ТӨЛЕПБЕРГЕН ҚАЙЫПБЕРГЕНОВТЫҢ ДӨРЕТИЎШИЛИГИНДЕ ИНСАН КОНЦЕПЦИЯСЫ ТИПОЛОГИЯСЫ - Бекбергенова, М.Д. (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of creating a person’s image in the creative work of the people’s writer of Uzbekistan and Karakalpakstan, the great writer of the XX th century Karakalpak prose T.Kayipbergenov. There have been analysed such qualities as humanity, purity of soul, truthfulhess, honesty, good and evil, the broadness of the inner world of a person, as well as the narrowness of the human look in some concepts.
Keywords: image; story; novel; humanity; purity; devotion